Growth and viability of juvenile humpback grouper (Cromileptes altivelis) supplemented with inorganic and organic selenium - Hamzah, Muhaimin; Suprayudi, Muhammad Agus; Utomo, Nur Bambang Priyo; Manalu, Wasmen (Jurnal Akuakultur Indonesia, 2012)
This study was conducted to determine the effects of inorganic selenium (sodium selenite) and organic selenium (selenomethionine) supplementation on growth and viability of juvenile humpback grouper (Cromileptes altivelis). The experiment was designed as a completely randomized design with eight treatments and three replications. The treatment being tested was source and dosages of selenium ie., inorganic selenium (sodium selenite) supplementation with dosages of 0.5, 1, 2, and 4 mg Se/kg diet and organic selenium (selenomethionine) with dosages of 1, 2, and 4 mg Se/kg diet. Another treatment was unsupplemented selenium. Juveniles humpback grouper at an initial average length of 6,39±0,41 cm and body weight of 4,49±0,65 g were reared in 90×40×35 cm3 aquaria and fed artificial diet (pellet) two times daily (08.00 and 16.00) at satiation. Fishes were reared for 40 days at a stocking density of 12 fish per aquarium on sea water with salinity of 30–31 ppt and temperature of 28–29 °C. The results of this study showed that the source of selenium supplementation (inorganic or organic) affected growth performance, glutathione peroxidase (GPx) enzyme activity, and blood profiles of the experimental fish. Generally, it was found that selenomethionine supplementation resulted in better fish performance than sodium selenite. In sodium selenite supplementation, survival declined with the increased dosages of Se in the diet, and the supplementation at dosage of 0,5 mg Se/kg diet showed a toxic effects. Histopatological test showed that there were damage in livers, kidneys, and intestines of fish supplemented with sodium selenite from 0.5 to 4 mg Se/kg diet. On the contrary, supplementation of selenomethionine up to 4 mg Se/kg did not show any signs of toxicity and the survival was on 86.11 to 97.22%. Feed efficiency, protein retention, lipid retention, and Se retention indicated that a dosage of 4 mg Se/kg selenomethionine supplementation was the best dosage.Keywords: selenium, viability, growth, Cromileptes altivelis, humpback grouper